Analysis Study To Gratitude And Parenting Stress On Parents Of Children With Special Needs - Epifania M. Ladapase; Maria Nona Nancy (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Parenting can provide many satisfactions while also presenting many challenges. The aim of this research is to determine the effect of gratitude on parenting stress in parents who have children with special needs. The method used is a quantitative research method. The sample in this study amounted to 56 people. The measuring instruments used are the gratitude scale and the parenting stress scale. The results of data analysis show that there is an influence of gratitude on parenting stress in parents of children with special needs with an R value of 0.388 at a significant level of 0.000 (p<0.05. The strength of the influence of gratitude on parenting stress is 11.4%, the remaining 88.6% is influenced by factors others not examined in this research. The hypothesis in this research is accepted. Keywords: gratitude, parenting stress, parents, children with special needs